Migraine and Tension-Type Headache Among Children and Adolescents: Application of International Headache Society Criteria in a Clinical Setting. (July 2021) - Genizi, Jacob; Bugdnoskya, Vera; Aboud, Amer; Segal, Idan; Assaf, Nurit; Srugo, Isaac; Kerem, Nogah C.
Introduction: The International Headache Society criteria were written in order to help physicians establish a headache diagnosis. However, sometimes children with headache do not seem to fit any diagnosis. The purpose of our study was to assess the application of the criteria in a clinical setting. Methods: Medical records of children referred for primary headache to the pediatric neurology clinic at Bnai Zion Medical Center from 2008 to 2017 were assessed. Results: A total of 989 patients (range 6-18 years; 53% female) were assessed at our neurology clinic. Twenty-four percent (n = 241) were diagnosed with tension-type headache, 26% (n = 256) with migraine, and 4.5% (45) with mixed headache. In 41.5% (410), we were unable to reach a specific diagnosis. No differences in gender or age were found between the groups. Children in the migraine group used more analgesic treatments to stop the headache attacks compared with the tension-type headache group (50% vs 38%, P = .001). Patients diagnosed with tension-type headache reported having more emotional difficulties ( P = .001). No significant differences were found in headache characteristics (ie, location, sidedness, character), frequency, or intensity between the younger children (ages 6-11) and the adolescents (ages 12-18) within either the tension-type headache or migraine groups. Conclusions: Retrospective application of International Headache Society criteria in a large cohort of children with headaches failed to diagnose a specific type of headache in 41.5% of children. Migraine and tension-type headache were equally prevalent, and both constituted a major burden on our patients' everyday lives. We found no major differences in frequency, intensity, and characteristics of pain between younger children and adolescents.